Efficacy of knowledge and competence-based training of non-physicians in the provision of early infant male circumcision using the Mogen clamp in Rakai, Uganda - Kankaka, Edward Nelson; Kigozi, Godfrey; Kighoma, Nehemiah; Murungi, Teddy; Gray, Ronald H. (BJU international, 2017)
To assess acquisition of knowledge and competence in performing Early Infant Male Circumcision (EIMC) by non-physicians trained using a structured curriculum. Training in provision of EIMC using the Mogen clamp was conducted for 10 Clinical Officers (COs) and 10 Registered Nurse Midwives (RNMWs), in Rakai, Uganda. Healthy infants whose mothers consented to study participation were assigned to the trainees, each of whom performed at least 10 EIMCs. Ongoing assessment and feedback for competency were done, and safety assessed by adverse events. Despite similar baseline knowledge, COs acquired more didactic knowledge than RNMWs (P = 0.043). In all, 100 EIMCs were assessed for gain in competency. The greatest improvement in competency was between the first and third procedures, and all trainees achieved 80% competency and retention of skills by the seventh procedure. The median (interquartile range) time to complete a procedure was 14.5 (10–47) min for the COs, and 15 (10–50) min for the RNMWs (P = 0.180). The procedure times declined by 2.2 min for each subsequent EIMC (P = 0.005), and rates of improvement were similar for COs and RNMWs. Adverse events were comparable between providers (3.5%), of which 1% were of moderate severity. Competence-based training of non-physicians improved knowledge and competency in EIMC performed by COs and RNMWs in Uganda.